2003
DOI: 10.1007/s00259-003-1211-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of [ 18 F]FDG PET in characterising renal cancer and detecting distant metastases: a comparison with CT

Abstract: The purpose of this study was to assess the efficiency of fluorine-18 fluoro-2-deoxyglucose (FDG) positron emission tomography (PET) in the characterisation and primary staging of suspicious renal masses, in comparison with computed tomography, the current standard imaging modality. Fifty-three FDG PET studies were performed within the framework of a prospective study: 35 for both characterisation and staging of a suspicious mass, and 18 for staging early after surgical removal of a renal cancer. In the charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(115 citation statements)
references
References 15 publications
3
112
0
Order By: Relevance
“…The accuracy of 18 F-FDG PET/CT in detecting distant metastasis was 94%, while the accuracy of ceCT was 89%. They emphasized that 18 F-FDG PET is especially needed for metabolic characterization if there is a solitary suspected lesion in a local advanced case [10]. In our study, although a detailed analysis of disease stage was not possible in all patients, 3 patients with distant metastasis had extensive lymphovascular invasion reported in the nephrectomy material.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The accuracy of 18 F-FDG PET/CT in detecting distant metastasis was 94%, while the accuracy of ceCT was 89%. They emphasized that 18 F-FDG PET is especially needed for metabolic characterization if there is a solitary suspected lesion in a local advanced case [10]. In our study, although a detailed analysis of disease stage was not possible in all patients, 3 patients with distant metastasis had extensive lymphovascular invasion reported in the nephrectomy material.…”
Section: Discussionmentioning
confidence: 76%
“…The data reported by Aide et al, revealed that 18 F-FDG PET/ CT is an effective method for evaluation of distant metastasis in the early postoperative staging of RCC [10]. The accuracy of 18 F-FDG PET/CT in detecting distant metastasis was 94%, while the accuracy of ceCT was 89%.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies also noted that oncocytomas can yield false positive results on F-18 FDG-PET/CT [21,41]. [180,181] In a study by Goldberg et al [182], patients with indeterminate renal cysts were examined and F-18 FDG-PET/CT accurately detected 10 cysts as benign with no false positive results.…”
Section: Nuclear Imaging and Differentiation Of Renal Massesmentioning
confidence: 99%
“…FDG is excreted by the kidney, which may mask pathologic uptake. In a prospective study, Aide et al [31] found a high rate of false-negative results when localized RCC was considered (Fig. 4).…”
Section: Positron Emission Tomographymentioning
confidence: 99%